2013
DOI: 10.1002/btpr.1855
|View full text |Cite
|
Sign up to set email alerts
|

Pathway analysis of Pichia pastoris to elucidate methanol metabolism and its regulation for production of recombinant proteins

Abstract: This research rationally analyzes metabolic pathways of Pichia pastoris to study the metabolic flux responses of this yeast under methanol metabolism. A metabolic model of P. pastoris was constructed and analyzed by elementary mode analysis (EMA). EMA was used to comprehensively identify the cell's metabolic flux profiles and its underlying regulation mechanisms for the production of recombinant proteins from methanol. Change in phenotypes and flux profiles during methanol adaptation with varying feed mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
10
0
5
Order By: Relevance
“…As the most important energy source for metabolic pathways, ATP plays a vital role in cell growth and the production of the target products by affecting peptide folding, stress response, transportation, metabolic flux, and signal transduction [3335]. A prior study had shown that approximately four ATP equivalents were required to form each polypeptide bond of GFP, and the amount of ATP needed from the intermediate metabolism to produce one unit of GFP was 333 [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the most important energy source for metabolic pathways, ATP plays a vital role in cell growth and the production of the target products by affecting peptide folding, stress response, transportation, metabolic flux, and signal transduction [3335]. A prior study had shown that approximately four ATP equivalents were required to form each polypeptide bond of GFP, and the amount of ATP needed from the intermediate metabolism to produce one unit of GFP was 333 [35].…”
Section: Resultsmentioning
confidence: 99%
“…A prior study had shown that approximately four ATP equivalents were required to form each polypeptide bond of GFP, and the amount of ATP needed from the intermediate metabolism to produce one unit of GFP was 333 [35]. Thus, the requirement of ATP is larger in C .…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic networks of the different organisms (Komagataella phaffii formerly Pichia pastoris, Saccharomyces cerevisiae, Escherichia coli, Bacillus subtilis, Corynebacterium glutamicum, Cupriavidus necator formerly Ralstonia eutropha and Clostridium autoethanogenum) were modified from published stoichiometric network analyses (Melzer et al, 2009;Lopar et al, 2013Lopar et al, , 2014Ternon et al, 2014;Unrean, 2014;Kracke et al, 2016;Koch et al, 2017; to fulfill the requirements of this elementary flux mode analysis. Specifically, the networks were integrated with methane assimilation pathways, compiled as follows:…”
Section: Construction Of Metabolic Networkmentioning
confidence: 99%
“…Several studies about metabolic engineering in P . pastoris portrayed the regulatory aspects of intracellular metabolic reactions and development in recombinant protein production [ 3 , 4 ]. In these, it was reported that the metabolic stress response against overexpression of recombinant protein redirects the intracellular carbon metabolism towards precursor formation to satisfy the increased energy demand.…”
Section: Introductionmentioning
confidence: 99%